The Relationship Between Mother's Communication Skills and Social-Personal Development of Preschool-Age Children - Halmina Ilyas; Nour Sriyanah; Suradi Efendi; Andi Ainul Suras (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Obesity is a condition in which body fat is in excessive amounts. Obesity is a risk factor for the 5th leading cause of death in the world. About 2.8 million people in the world die from complications of obesity, 23% suffer from ischemic heart disease, and 7% to 41% have a risk of developing cancer in certain organs. This study aims to determine the relationship between lifestyle and obesity in adolescents at SMPN 1 Bulukumba in 2021. The type of research used is an observational study with a cross sectional design. The sampling technique was purposive sampling. The population in the study was 352 people. The sample in this study were 47 people. Analysis of eating patterns with obesity using the square test obtained a value (p = 0.000) indicating that there is a significant relationship between diet and the incidence of obesity and on physical activity the value (p = 0.049) shows that there is a relationship between physical activity and the incidence of obesity in Junior High School 1 Bulukumba youth. The conclusion in this study is that there is a relationship between diet and physical activity with the incidence of obesity in adolescents at SMP Negeri 1 Bulukumba. It is recommended for adolescents to behave in a healthy life by maintaining a good diet and managing physical activity properly in order to avoid various degenerative diseases due to complications from obesity.